Two methods for the quantitative analysis of surface antigen expression in acute myeloid leukemia (AML). - Jolanta Woźniak (Folia Histochemica et Cytobiologica, 2004)
The expression of lineage molecules (CD13 and CD33), c-Kit receptor (CD117), CD34, HLA-DR and adhesion molecule CD49d was assessed in acute myeloid leukemia (AML) blast cells from 32 cases, using direct and indirect quantitative cytometric analysis. High correlation (r=0.8) was found between antigen expression intensity values calculated by direct analysis method (ABC) and by indirect analysis method (RFI). Moreover, the differences in expression intensity of CD13, CD117 and CD34 antigens were found between leukemic and normal myeloblasts. This may be helpful in identification of leukemic cells in the diagnostics of minimal residual disease after treatment in AML patients.